Influence of dietary fat on duodenal resistance to acid. - Lugea, A (1993)
Three experimental diets were prepared from a standard formula plus pure oleic, linoleic, or eicosapentaenoic acid (2% by weight). Mucosal resistance to acid was tested in anaesthetised rats fed the experimental diets for at least four weeks (60 rats per diet) by duodenal infusion of HCl (200 to 700 mumol) 30 minutes after pretreatment with either saline or 100 mumol HCl (used as a mild irritant). Rats were killed one hour after the test and the duodenal damage was assessed 'blindly' using a combined macroscopic and histological score. Differences were tested by analysis of covariance of the dose-response curves. Mucosal resistance was similar in the three groups when the acid challenge was given after saline pretreatment. Resistance to acid in all three groups was significantly increased by previous exposure to 100 mumol HCl (p < 0.01). Interestingly, rats fed a linoleic or eicosapentaenoic supplemented diet after pretreatment with HCl developed significantly higher resistance to acid than those fed the diet with oleic acid (p < 0.05). Pretreatment with indomethacin suppressed the difference between diets. In conclusion, dietary polyunsaturated fatty acids enhance duodenal resistance to acid by potentiation of adaptive cytoprotection.